Correlation of interactive learning and students' intellectual emotion / Gladys Tagie ... [et al.] - Tagie, Gladys; Merman, Hairulnisak; Taharuddin, Nurul Shima; Johari, Rozarina (Universiti Teknologi MARA, Perak, 2023)
This research aims to explore the correlation between interactive learning methods and students' intellectual emotions conducted on the subject VCS 105 (An appreciation of art and design history), a compulsory subject for the first-semester Diploma of Creative art. This subject requires deep understanding, memorizing art history, facts, and characters of art globally throughout the ages. The biggest problem in teaching and learning in the new norm is attracting attention from students along with the rapid development of technology. As an educator, we need to creatively change the teaching method from traditional method to Online based education. The interactive learning method is proposed as an effective approach to gain a short-term attention span among students. Finally, the researcher can evaluate students' perceptions of learning in class as well as their level of acceptance of the knowledge that has been delivered. In this study, online game-based interactive learning has been specially designed creatively to obtain the extent of the effectiveness of teaching and learning. The researcher used the Quiz Whizzer online application as a main pillar of this study. Quiz Whizzer is a website-based application as an online educational game that provides easy means in the learning process. Furthermore, Quiz Whizzer is a game-based learning platform, used as educational technology in educational institutions. The focus of this activity is the use of making interactive games, developing social skills, and relationships among group members. This gamification creatively combines the technology of QR codes to solve the puzzle online. The implementation of interactive learning, not only develops the interpersonal relations between students but also demonstrates their active participation in class. The findings of this study demonstrated that these students have a positive attitude toward learning. For instance, they believe that applying interactive learning such as online games in a subject will improve their knowledge. Most importantly, the result of this study revealed the effectiveness of interactive learning in relation to the intellectual emotion of students.